2021
DOI: 10.1111/ajt.16198
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of accepting kidneys from older donation after cardiac death donors

Abstract: Kidneys from older (age ≥50 years) donation after cardiac death (DCD50) donors are less likely to be transplanted due to inferior posttransplant outcomes. However, candidates who decline a DCD50 offer must wait for an uncertain future offer. To characterize the survival benefit of accepting DCD50 kidneys, we used 2010‐2018 Scientific Registry for Transplant Recipients (SRTR) data to identify 92 081 adult kidney transplantation candidates who were offered a DCD50 kidney that was eventually accepted for transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…After adjusting for other variables, accepting a DCD50 kidney was associated with a decreased mortality risk compared with declining the offer (adjusted HR [aHR] = 0.51, 95% CI = 0.46-0.55, P < .001). 42 Arcos et al reported a similar finding when considering kidney donors ≥80 years old. Of 2858 kidney transplant candidates ≥60 years old, 1084 received a kidney from a donor 60 to 79 years old, and 128 from a donor ≥80 years old.…”
Section: Donor Factorsmentioning
confidence: 56%
See 1 more Smart Citation
“…After adjusting for other variables, accepting a DCD50 kidney was associated with a decreased mortality risk compared with declining the offer (adjusted HR [aHR] = 0.51, 95% CI = 0.46-0.55, P < .001). 42 Arcos et al reported a similar finding when considering kidney donors ≥80 years old. Of 2858 kidney transplant candidates ≥60 years old, 1084 received a kidney from a donor 60 to 79 years old, and 128 from a donor ≥80 years old.…”
Section: Donor Factorsmentioning
confidence: 56%
“…The survival benefit of kidney transplantation has been well-established and extended to include organs from a wider pool of donors. 42,43 However, kidney transplant recipients continue to have an elevated risk of MACE than the general population. 44 Using the National Inpatient Sample database, Goyal and associates identified 147 431 kidney transplants from 2004 to 2013.…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…In 2021, 144,302 organ transplants were completed worldwide (11.3% increase over 2020). In 2021, China has completed 19,386 organ transplants, ranking as one of the world's four major organ transplant countries with the United States (42,217), Brazil (7,088) and Spain (4,781). Organ transplants in these four countries accounts for more than 50% of the world [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the survival benefit of kidney grafts from DCDs with expanded criteria is more controversial. A recent analysis of Scientific Registry of Transplant Recipients (SRTR) data has observed that recipients of kidney grafts from DCDs ≥60 years of age have a 48% lower risk of death than patients who remained on the waiting list [ 21 ]. In contrast, the Dutch Organ Transplantation Registry reported that the mortality rate of elderly recipients receiving a kidney graft from a DCD ≥65 years of age was higher than for similarly old patients on the waiting list [ 22 ].…”
Section: Introductionmentioning
confidence: 99%